Agrarian-Economic Structure of Agricultural Holdings in Poland and East Germany: Selected Elements of Comparative Analysis - Jezierska-Thöle, Aleksandra; Janzen, Jörg; Rudnicki, Roman (Quaestiones Geographicae, 2014)
The aim of this study was to determine differences in the development of farms in Poland against the agriculture of East Germany, and to show areas with similar conditions for development. The time range of the research covered the years 2002-2010, i.e. the stage of preparation of Polish agriculture for accession to the European Union, the implementation of pre-accession aid programmes, and the establishment and implementation of the tools of the Common Agricultural Policy. To assess the level of agricultural development, natural, productive and social characteristics were adopted. Spatial variations in the analysed features were based on the variation coefficient (Vz), and the level of agricultural development, on Perkal’s index (Wi). In the analysed period the range of variation and the degree of the spatial dispersion of sub-indices changed, indicating a deepening of the polarisation processes in agriculture. The implementation of CAP intensified the process of specialisation and modernisation in agriculture, an example of which is the increase in the average farm size and in agricultural productivity. On the other hand, agricultural production intensified, as exemplified by a decrease in the minimum value in six of the analysed characteristics, which indicates growing disparities.